(untitled) (Innovative Teaching and Learning Journal, 2023)
This paper aim to investigate on type of student’s interaction in learning Research Methodology course through a mobile learning environment. A qualitative research design was used in this study and data was collected from ten postgraduate students (purposive sampling) who have enrolled in a social science research course for one semester. Face-to-face interviews were conducted to collect the qualitative data to gather comprehensive information for this study. The findings and discussions in this study relate to five types of student interactions which are learner-learner, learner-instructor, learner-content, learner-self and learner-interface in the development of a mobile learning environment for a social science research course. The study concludes that student roles, instructor roles, learning tools, learning activities, and learning materials are important criteria to consider when developing student interactions, especially for social science researchers, in a mobile learning environment. In conclusion, this paper discusses four limitations and makes recommendations for future studies.